Monte Carlo Simulation of on-Street Parking Retribution Revenue Potential in Sleman Regency Indonesia - Soejanto, Irwan; Soejanto, Soejanto; Dwi Astanti, Yuli (International Journal of Engineering and Technology, 2018)
Regional autonomy in Indonesia allows every region in Indonesia to manage its own finances. Each region shall be entitled to regulate their own locally-generated revenue, including taxes and user charges. One source of regional levies is from Public On-street parking. On-Street parking in Sleman Regency Yogyakarta has considerable potential. Sleman is a district with the largest population in DI Yogyakarta province of Indonesia. This is because most of the commercial, educational, health and employment centers are located in Sleman. There are several On-street parking centers in Sleman, and the most are in Depok District. So far, the parking retribution system of On-street parking is one of the sources of locally-generated revenue is to determine the value of certain contracts that must be paid by the parking operator to the government. The value of this contract is fixed monthly for one year and will be reviewed in the following year. The value of this fixed contract indicates the number and types of vehicles coming at that location are fixed every day. For example, if the parking rate of two-wheeled vehicles is IDR 1000 and the monthly contract value is IDR 400,000 then the parking location will only contain a maximum of 13 motorcycles every day. In fact, the frequency of vehicles and vehicle types is a variable that is probabilistic in nature. Therefore, this study will attempt to simulate the potential revenue of parking charges by entering on-street parking probabilistic elements. The result of this research is the combination and number of parking vehicles obtained from simulation result. This simulation model can then be used as a predictor of the potential revenue from on-street parking charge so that it can also be used to determine a more appropriate contract value policy.